Pemberdayaan Teknologi Tepat Guna Melalui Pelatihan Pembuatan Website Untuk UMKM Peyek Bayam Yusr di Desa Rajabasa Lama I, Lampung Timur - Mutia Anjani (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service activity was carried out to increase the digital capacity and expand the market reach of the Peyek Bayam Yusr MSME located in Rajabasa Lama I Village, East Lampung, through the application of appropriate technology in the form of website creation and management training. In the rapidly developing digital era, the presence of online media is a key factor in supporting product marketing, but most MSMEs in this region do not yet have the skills or knowledge to utilize it optimally. This activity was designed in several stages: identifying needs, socialization, technical training, mentoring, and evaluation. The training included creating an account on a free platform, selecting a template, filling in product content, and managing supporting features such as photo galleries, contact information, and integration with social media. This approach was carried out directly by students so that MSME owners could follow each process. The results showed that after the training, all participants were able to create a simple website and began using it for promotions. Identified direct impacts included increased product visibility in online media, increased orders, and demand from outside areas that were previously difficult to reach. In addition, this activity also encouraged a shift in marketing patterns from conventional methods to technology-based strategies. The analysis of the results indicates consistency with various previous studies, such as Santoso (2020) and Ginting et al. (2021), which emphasize the importance of MSME digitalization to increase competitiveness. This process has had a significant positive impact on MSMEs. This program is recommended for other MSMEs, as it is hoped that this program will have a positive impact in line with market needs. This process is accompanied by direct mentoring so that the achieved results can be maintained and developed